Medical tourism in India: an exploratory study - Reddy, Sumanth Gopala (Kansas State University, 2013)
Medical tourism comprises a phenomenon where over five million patients a year are traveling across international borders to obtain various forms of health care. Most of these patients travel from developed countries to developing countries, seeking highly invasive medical treatments to less invasive and recreational medical procedures. By the year 2012, the medical tourism industry generated over $100 billion with over 50 countries making it a priority in trade for their country. With active government promotions, India has become one of the leading destinations for medical tourism. The objective of this research was to answer the questions: 1) how do the attitudes and behaviors of patients towards the concept of medical tourism influence their decision to become a medical tourist; 2) why do medical tourists seek treatment in India; and 3) what are the issues and challenges they face before coming to India as well as while in India. Interviews of thirty-four foreign patients were conducted in six sites spread across the South-Indian cities of Bangalore, Hyderabad, and Chennai which revealed useful information in addressing the research objectives. The three most important reasons that these medical tourists chose India for their treatments were: 1) the high quality of the doctors and medical facilities in India, 2) the affordable cost of treatments, and 3) the availability of specific treatments that might not have been available in their home countries. Patients also researched the topic thoroughly before they came to India. Knowledge was gained primarily from the Internet, print media, television shows and friends. Overall, the patients had very positive attitudes towards medical tourism. Most of them felt that they could get treatment because of their positive opinion on medical tourism, their ability to get treatment if they desired, and support from their families and loved ones.
Keywords: Medical tourism; India; Theory of planned behavior; Therapeutic landscape; Patient knowledge; Cost; Geography (0366); Health Care Management (0769); Recreation and Tourism (0814)